Atopic dermatitis complicated by severe impetigo in a Syrian refugee infant. (14th May 2018) - Green, Peter; Munn, Elizabeth
Abstract : We present the case of a 3-month-old infant with atopic dermatitis who developed severe impetigo. The child was born to Syrian refugees shortly after they arrived in Canada. The case demonstrates the rapid and nearly complete resolution of dramatic skin findings after a course of hydrocortisone ointment and oral antibiotics with adjuvant measures. For resettled refugees, access to family physicians and local language proficiency are common barriers that negatively impact their health and healthcare. We discuss some aspects of how the healthcare model in one Canadian city addresses these issues in the context of this case. The case also raises questions about the burden of dermatological conditions in refugees while in transit and in countries of resettlement. The few reports that exist suggest that some conditions may be relatively common and that the epidemiology warrants additional investigation.